Strategi Pemasaran Wafer Ransum Komplit untuk Ternak Sapi - Udoh Roudotul Jannah; - Suryahadi; Hartrisari Hardjomidjojo (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2013)
This research was aimed to analyze level of interest, identify significant predictor for intention to purchase, analyze level of uniqueness, analyze level of concordance and develop marketing strategy for wafer complete ration. The research design used judgmental sampling to select 30 respondent in Jakarta, Bogor, Depok, Tangerang and Bekasi. The data were analyzed by using descriptive analysis and ordinal regression. The result showed that wafer complete ration concept was well received. This is indicated by the level of interest (57%) of farmers to the concept. However, there are only 47% of farmers who have a desire to buy a wafer complete ration. Predictors variable that increasing level of willingness to buy are level of uniqueness, whether or not never use agriculture waste and the most usage of feed. While the other predictor variables influence to decrease level of willingness to buy are level of concordance between concepts and needs, level of interest, whether or not never heard about wafer complete ration, number of cattle and the last length of cattle business. Marketing strategies include product development, prices in the range of Rp4500 to Rp5500, the distribution system will be used broken off sell and promotion strategies with more emphasis on activities below the line